A two stage approach to antibacterial activity of wastewater using annealed Zn0.5Mn0.5O nano-composites - M. Yasir Ali; S. Younus; N. Amin; Adnan Ali; Muhammad Isram; S. Ikram; K. Mahmood; M. Junaid Dilshad (Results in Chemistry)
In this manuscript, Zn0.5Mn0.5O nano-particles were used to treat the water of Faisalabad wastewater treatment facility using double approach, i.e. making composite with Mn metal and post growth annealing technique. Zn0.5Mn0.5O were synthesized using the hydrothermal method and post growth annealed at temperatures ranging from 150 to 650 °C. After the structural and bonding verification by XRD and Raman measurements, the grown samples were used to treat the wastewater. A 50 mg of Zn0.5Mn0.5O powder was mixed with 10 ml of wastewater and a drop of mixture was spread over LB agar plates for the plate count method to measure colony forming units (CFU) of samples. It was observed that wastewater solution containing Zn0.5Mn0.5O powder, which was annealed at 150 °C contained only few bacteria. But the solutions having high temperature annealed Zn0.5Mn0.5O nano-composites showing large colonies of pathogens. To confirm this behavior, we have also used the disc diffusion method. It was again found that Zn0.5Mn0.5O nano-composite annealed at 150 °C possessed the large inhabitant bacteria zone as compared to other samples. Most of the pathogens were found killed by making composition and remaining were killed by annealing process. It was also found that the anti-bacterial activity was found to be decreased with increasing annealing temperature because of occupation of oxygen vacancies, which resulted in the reduction of reactive oxygen species (ROS).